(x + 3y - 5z) - (x - 3y + 4z)

Remember, subtracting a quantity N is the same as adding -N = -1*N.

In this case:

(x + 3y - 5z) - (x - 3y + 4z)

= (x + 3y - 5z) + (-1)(x - 3y + 4z)

= (x + 3y - 5z) + (-x + 3y - 4z)

= 6y - 9z

(x + 3y - 5z) - (x - 3y + 4z)

Tutors, please sign in to answer this question.

Remember, subtracting a quantity N is the same as adding -N = -1*N.

In this case:

(x + 3y - 5z) - (x - 3y + 4z)

= (x + 3y - 5z) + (-1)(x - 3y + 4z)

= (x + 3y - 5z) + (-x + 3y - 4z)

= 6y - 9z

Timothy R.

Effective Mathematics and Physics Tutor

Avenel, NJ

4.9
(99 ratings)

Richard W.

Yale PhD Grad for Science & Writing Tutoring + SAT ACT SATII Test Prep

New York, NY

5.0
(51 ratings)